2004
DOI: 10.1073/pnas.0400339101
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 plays a central role in Th2 differentiation

Abstract: Differentiation of naïve CD4 T cells into T helper (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
363
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(383 citation statements)
references
References 43 publications
19
363
1
Order By: Relevance
“…For Th2 differentiation, Stat6 activation is necessary and sufficient to transduce IL-4 signaling, at least in vitro [9][10][11]. IL-2 mediated Stat5 activation is also critical for this process [12,13]. In this review, many recent reports by our laboratory…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…For Th2 differentiation, Stat6 activation is necessary and sufficient to transduce IL-4 signaling, at least in vitro [9][10][11]. IL-2 mediated Stat5 activation is also critical for this process [12,13]. In this review, many recent reports by our laboratory…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Cote-Sierra et al have shown that IL-2 is not required for T cell proliferation and/or survival if IL-4 is added in the culture [12]. Thus, when naïve 5C.C7 CD4 T cells, derived from Rag2 -/-TCR transgenic mice, in which the TCR is specific for pigeon cytochrome C (PCC), were primed under Th2 conditions in vitro (peptide or anti-CD3/anti-CD28 plus IL-4, anti-IL-12 and anti-IFNγ), the proliferative rate, as judged by CFSE dilution, of the cells primed in the absence of IL-2 signaling (through the addition of anti-IL-2 and anti-IL-2Rα) was similar to that of the cells primed in the presence of IL-2, as was the total cell yield.…”
Section: Il-2 and Stat5 In Th2 Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…As such both effector and regulatory T cells require IL-2 for growth and differentiation (Le Gros et al, 1990;Papiernik et al, 1998;Cote-Sierra et al, 2004;Fontenot et al, 2005;Yamane et al, 2005). Thus the presence or up-regulation of CD25 cannot unequivocally distinguish Treg from activated effector T cells.…”
Section: Cd25mentioning
confidence: 99%
“…IL-2 is central to Th2 and Treg cell differentiation and proliferation (Cote-Sierra et al, 2004;de la Rosa et al, 2004). As receptors for IL-2 subunits (e.g.…”
Section: Interleukin-2 Sequestrationmentioning
confidence: 99%